Taxonomic notes on species of the genera Agelena Walckenaer, 1805, Tamgrinia Lehtinen, 1967 and Tegenaria Latreille, 1804 from India, with remarks on an allied species from Nepal (Araneae: Agelenidae) - Sudhin, Puthoor Pattammal; Sankaran, Pradeep M.; Sen, Souvik (Zootaxa, 2026)
The species belonging to Agelena Walckenaer, 1805, Tamgrinia Lehtinen, 1967 and Tegenaria Latreille, 1804 described or recorded from India are reviewed. The following new synonymies are recognised: Agelena shillongensis Tikader, 1969 syn. nov. with Tegenaria domestica (Clerck, 1757), and Tegenaria comstocki Gajbe, 2004 syn. nov. with the titanoecid species Pandava laminata (Thorell, 1878). The synonymy of the Indian species Tegenaria chhanguensis Tikader, 1970 with the Chinese species Tamgrinia alveolifera (Schenkel, 1936) as proposed by Hu (2001), is confirmed based on an examination of the type specimen of the former one. The species Agelena satmila Tikader, 1970, Tegenaria hemanginiae Reddy & Patel, 1992, and T. shillongensis Barman, 1979 are considered species inquirendae. The Nepalese agelenid species Tegenaria lunakensis Tikader, 1964 is transferred to Draconarius Ovtchinnikov, 1999: D. lunakensis (Tikader, 1964) comb. nov. Photographs of all the examined type material, and supplementary descriptions for Agelena barunae Tikader, 1970, A. gautami Tikader, 1962, A. satmila, and D. lunakensis comb. nov. are provided.